Kinetic modelling during soaking of dried long grain paddy MR297 - Muchlisyiyah, Jhauharotul; Shamsudin, Rosnah; Kadir-Basha, Roseliza; Shukri, Radhiah; How, Syahmeer; Rambli, Masmunira (University of Brunei Darussalam, 2024)
This study aimed to assess the soaking behaviour of MR 297 dried paddy under two conditions: room temperature and hot water soaking at 60 ∘C. The experiment involved soaking dried MR297 paddy samples in water for 0.5e8 h at room temperature and 0.5e5 h for soaking at 60 ∘C. The water absorption of MR 297 behaved differently at two different soaking conditions. The kinetic behaviour of the soaking process was also simulated using established 25 predictive models and incorporating 5 novel models presented in this work. The comparison of all prediction models involved using three statistical measures: the coefficient of determination (R-squared), standard error of estimates (SEE), and root mean square error (RMSE). The Karizaki 10, Midilli Kucuk, Karizaki 8, Two term, and Proposed Model was determined to be the 5 of most effective predictive models for characterizing the MR297 paddy soaking behaviour at room temperature. While Cubic, Karizaki 11, Karizaki 10, Karizaki 8, and proposed model 5 provided superior predictive capabilities for soaking behaviour of MR 297 at 60 ∘C. Additionally, the findings of this study also indicate that the proposed models exhibit superior predictive performance compared to the convenational models employed by other researchers.